Effects of thermal treatments on microstructure and mechanical properties of a Co–Cr–Mo–W biomedical alloy produced by laser sintering. (July 2016) - Mengucci, P.; Barucca, G.; Gatto, A.; Bassoli, E.; Denti, L.; Fiori, F.; Girardin, E.; Bastianoni, P.; Rutkowski, B.; Czyrska-Filemonowicz, A.
Abstract: Direct Metal Laser Sintering (DMLS) technology based on a layer by layer production process was used to produce a Co–Cr–Mo–W alloy specifically developed for biomedical applications. The alloy mechanical response and microstructure were investigated in the as-sintered state and after post-production thermal treatments. Roughness and hardness measurements, and tensile and flexural tests were performed to study the mechanical response of the alloy while X-ray diffraction (XRD), electron microscopy (SEM, TEM, STEM) techniques and microanalysis (EDX) were used to investigate the microstructure in different conditions. Results showed an intricate network of ε -Co (hcp) lamellae in the γ -Co (fcc) matrix responsible of the high UTS and hardness values in the as-sintered state. Thermal treatments increase volume fraction of the ε -Co (hcp) martensite but slightly modify the average size of the lamellar structure. Nevertheless, thermal treatments are capable of producing a sensible increase in UTS and hardness and a strong reduction in ductility. These latter effects were mainly attributed to the massive precipitation of an hcp Co3 (Mo, W)2 Si phase and the contemporary formation of Si-rich inclusions. Graphical abstract: Highlights: Co-based alloy with improved mechanical properties are produced by DMLS. A network of ε lamellae in γ matrix is present in the as-sintered sample. Thermal treatments increase both UTS and hardness while decreasing ductility. Mechanical response is influenced by the massive precipitation of Co3 (Mo, W)2 Si phase.